Broken safety pin in bronchus - Anaesthetic considerations - Shad, Roona (Medknow Publications & Media Pvt Ltd, 2012)
Safety pins are not commonly aspirated objects in infants and form only a small fraction of all the metallic foreign body (FB) which accounts for 4.4% of all foreign bodies found in tracheobronchial tree. Bronchoscopy procedure has various complications, in addition to failure to remove FB due to its impaction, especially with metallic pointed objects ending up in open surgical removal. Infant with inhaled foreign body are always a challenge to anaesthetist. We had one such case of broken safety pin impacted in the wall of right bronchus of an infant with failure to remove on repeated attempts at rigid bronchoscopy.